Forest Cover Mapping Using Interactive Dashboards with Google Earth Engine on Sentinel-2 Satellite Imagery - Nora Dzulvawan; Arie Wahyu Wijayanto (Proceedings of The International Conference on Data Science and Official Statistics, 2023)
The study aims to develop an attractive web-based visualization dashboard for mapping forest land cover around the world. The dashboard map was created using the Google Earth Engine application with JavaScript programming language. The built-in map dashboard has several interactive features, including legend, zoom, search, composite index view selection, visualization date selection, and wipers. The results of the dashboard black box test show that the dashboard works well and provides good visualization in mapping forest land cover for better monitoring and analysis.